Delirium, caused by suspending treatment of hypothyroidism - Alejandro Hernández-Sandí; David Quirós-Baltodano; Michelle Oconitrillo-Chaves (Mental Illness)
Delirium, or acute confusional syndrome, is a set of symptoms whose care involves not only psychiatry, but also many other medical specialties. Being as how the syndrome is caused by multiple factors, it is important to recognize each risk factor affecting the patient in order to anticipate and prevent it. In case of diagnosis, identifying and treating the root cause that triggered is important, given that it has a high rate of comorbidity and an elevated cost of medical care. We describe a case where a patient with hypothyroidism began suffering from delirium due to an abrupt discontinuation of levothyroxine treatment. Previously, the patient was seemingly healthy. After the medical treatment was interrupted, sensory processing and behavior were altered, and symptoms fluctuated, for a short period of time, showing disorientation and memory and language impairment.